Developing a value assessment index system of anti-tumour commercial Chinese polyherbal preparation in China: a modified Delphi study - Xia, Tongchao; Hu, Min; Luo, Chunmei; Yang, Mengmeng; Chu, Mingming; Xiang, Xing; Zhang, Zhe (Frontiers in Pharmacology, 2025)
ObjectiveTo develop a value assessment index system of anti-tumour commercial Chinese polyherbal preparation (CCPP).MethodsA modified two-round Delphi method was conducted to establish consensus within a field to reach an agreement via questionnaire among a multidisciplinary panel of experts. In addition, the analytic hierarchy process was used to conduct weight analysis of indicators.ResultsIn two rounds of Delphi consultation, the experts’ positive coefficient was over 90%, and the authoritative coefficient was over 0.70. The Kendall’s W of two rounds was 0.401 and 0.438, and the P-value of Kendall’s W test was all <0.001 for each round. The final value assessment index system consisted of 7 primary indicators, 24 secondary indicators, and 50 tertiary indicators.ConclusionThis value assessment index system could promote the clinical rational use of CCPP and the development of the drug catalog and clinical guideline in China.